Effects of olive leaf extract on exercise performance and muscle mitochondrial response in young healthy adults - Clément Lanfranchi; Nadège Zanou; Jérôme Feige; Umberto DeMarchi; Aurélie Hermant; Ornella Cominetti; Eugenia Migliavacca; Alba Moreno-Asso; Astrid Hostrman; Sara Mistro; Nicolas Place (Current Issues in Sport Science)
Introduction Sprint interval training (SIT) can elicit similar or even higher skeletal muscle mitochondrial adaptations than moderate-intensity continuous training (MICT) despite a lower training volume. We have previously shown that this is at least partially driven by improved skeletal muscle mitochondrial bioenergetics with increased mitochondrial Ca2+ uptake and pyruvate dehydrogenase (PDH) activation after a single session of SIT but not MICT [1]. Olive leaf extract (OLE) is a natural compound that triggers mitochondrial Ca2+ uptake and activates PDH in mouse skeletal muscle [2]. Here we tested the hypothesis that OLE would contribute to exercise performance improvement by increasing muscle mitochondrial response and PDH activation in human participants performing MICT.